Experience of Treatment of Iatrogenic Bile Duct Injuries Following Laparoscopic Cholecystectomy in Tertiary Care Hospitals of Khyber Pukhtunkhwa - Aamir Ali Khan, Saadia Nawaz Durrani, Faiz Ur Rahman, Fazal Hussain, Yasir Hussain, Sheikh Qais Falah, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: This research aims to learn how often iatrogenic bile duct injuries caused during laparoscopic cholecystectomy are treated and how well they heal after surgery. Study Design: A retrospective study Place and Duration: General Surgery Department of different hospitals of Khyber Pukhtunkhwa i.e Bacha Khan Medical Complex, Swabi, Peshawar Institute of Medical Sciences, Peshawar and Naseer Teaching Hospital, Peshawar for duration of two years from February 2020 to January 2022. Methods: In this research, 105 patients of both genders aged 18-68 years were enrolled. Included patients had iatrogenic bile duct injuries during laparoscopic cholecystectomy. Age, sex, place of residence, and body mass index were among the specific demographics of the enrolled cases that were calculated after receiving informed written consent. Strasberg classification was used to classify bile duct injuries. The outcome of treatment in all cases was measured in terms of effectiveness, complications, mortality and need for repeated treatment. SPSS 23.0 was used to analyze all data. Results: Among 105 presented cases, there were 68 (64.8%) females and 37 (35.2%) males. The mean age of the patients was 55.2±6.30 years and mean BMI 23.8±4.19 kg/m2. 55 (52.4%) patients were from urban areas. Most common symptom was epigastric pain, followed by fever, chills and jaundice. We found that Strasberg A was the most common injury found in 56 (53.3%) cases, followed by Strasberg D in 17 (16.2%) cases and Strasberg C in 12 (11.4%) cases. In all 105 cases, the majority of the patients received endoscopy in 67 (63.8%) cases and surgical treatment in 38 (36.2%) cases. Complications were bile leakage from the incision site, abdominal pain and bile leakage from the drain. Frequency of mortality was 4 (3.8%). Conclusion: We concluded in this study that the iatrogenic bile duct injuries were effectively treated with endoscopy and surgical treatment by using Strasberg classification. There was higher effectiveness and the mortality rate was low. Keywords: Iatrogenic Bile Duct Injury, Endoscopy, LC, Surgical, Mortality, Complications